2007
DOI: 10.1211/jpp.59.3.0011
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of oxidative stress status and antioxidant activity in chronic leukaemia patients

Abstract: There is an interactive relationship between leukaemia and oxidative stress. Leukaemic cells produce larger amounts of reactive oxygen species (ROS) than non-leukaemic cells as they are under a continual state of oxidative siege. So, this study was performed on 20 patients with chronic leukaemia from the Oncology Centre, Mansoura University. We measured leucocytic H(2)O(2) concentrations and lipid peroxidation as serum malondialdehyde (MDA) concentration, serum total antioxidant activity, plasma ascorbic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…These results are in accordance with the increase of TBARS levels in the serum of patients with chronic leukemia [24] and acute lymphoblastic leukemia [9, 25]. …”
Section: Discussionsupporting
confidence: 86%
“…These results are in accordance with the increase of TBARS levels in the serum of patients with chronic leukemia [24] and acute lymphoblastic leukemia [9, 25]. …”
Section: Discussionsupporting
confidence: 86%
“…This finding is consistent with several studies reporting that patients with hematological malignancies have a hyperoxidative state before any CR, suggesting an intrinsic process of the underlying disease or inherent to drug treatments prior to HSCT [11][12][13][14][15][16][17] . The CR with high-dose chemotherapy, to which the patients had been previously submitted, was able to exacerbate this hyperoxidative state.…”
Section: Discussionsupporting
confidence: 92%
“…Al-Gayyar et al (26) concluded that leukemia patients produce larger amounts of ROS than nonleukemia patients. Oltra et al (27) found that lymphocyte SOD and catalase activity is decreased in chronic lymphocytic leukemia, whereas GSH-Px activity is increased.…”
Section: Discussionmentioning
confidence: 99%